MmpL11 Protein Transports Mycolic Acid-containing Lipids to the Mycobacterial Cell Wall and Contributes to Biofilm Formation in Mycobacterium smegmatis - Pacheco, Sophia A. (American Society for Biochemistry and Molecular Biology, 2013)
A growing body of evidence indicates that MmpL (mycobacterial membrane protein large) transporters are dedicated to cell wall biosynthesis and transport mycobacterial lipids. How MmpL transporters function and the identities of their substrates have not been fully elucidated. We report the characterization of Mycobacterium smegmatis MmpL11. We showed previously that M. smegmatis lacking MmpL11 has reduced membrane permeability that results in resistance to host antimicrobial peptides. We report herein the further characterization of the M. smegmatis mmpL11 mutant and identification of the MmpL11 substrates. We found that biofilm formation by the M. smegmatis mmpL11 mutant was distinct from that by wild-type M. smegmatis. Analysis of cell wall lipids revealed that the mmpL11 mutant failed to export the mycolic acid-containing lipids monomeromycolyl diacylglycerol and mycolate ester wax to the bacterial surface. In addition, analysis of total lipids indicated that the mycolic acid-containing precursor molecule mycolyl phospholipid accumulated in the mmpL11 mutant compared with wild-type mycobacteria. MmpL11 is encoded at a chromosomal locus that is conserved across pathogenic and nonpathogenic mycobacteria. Phenotypes of the M. smegmatis mmpL11 mutant are complemented by the expression of M. smegmatis or M. tuberculosis MmpL11, suggesting that MmpL11 plays a conserved role in mycobacterial cell wall biogenesis.